Marketing Todays library - Brian Mathew (2014)
MOST LIBRARIANS DID NOT ENTER THIS profession because of a passion for marketing. Despite this, marketing skills have become a key element of a successful career in the field. At the same time, marketing itself has become far more complicated—it is no longer merely enough to craft a good message. To be successful today, a relevant marketer must also master the media through which his message is conveyed. In other words, this transformation of the role of librarian has happened during a time when it has never been more difficult to become an effective marketer. This challenge is not unique to your profession. In my field— e-commerce and distribution channel management—it took me about twelve years to admit that I was a marketer. My professional life has been focused on consumer-facing Internet (and other emerging media) business models since 1995, and my four patents all concern performance- based business models that are enabled by these media. Even so, for a long time I thought of myself as a general business manager who liked technology. Three years ago, I was rewarded for my e-commerce success by being given responsibility for the other distribution channels used by my company, InterContinental Hotels Group, in the Americas region. The name of our department was to become Distribution Marketing, a decidedly unsexy label that seemed to lack the geek-chic of my prior roles. However, after briefly considering a protest, I was finally forced to recognize that, as someone who spent all of his working life figuring out ways to influence consumer behavior, I was, in fact, a marketer and would just have to deal with it.